2023
DOI: 10.3389/fmolb.2023.1087982
|View full text |Cite
|
Sign up to set email alerts
|

New protocol for kinetic assay seeding ability recovery “KASAR” from formalin-fixed paraffin-embedded tissues

Abstract: The real-time quaking-induced conversion (RT-QuIC) alpha-synuclein (aSyn) protein kinetic seeding assay has been very useful for detecting pathological aggregates in various synucleinopathies including Parkinson’s disease (PD). This biomarker assay relies on fresh frozen tissue to effectively seed and amplify aSyn aggregating protein. With vast repositories of formalin-fixed paraffin-embedded (FFPE) tissues, it is paramount to harness the power of kinetic assays to unlock the diagnostic potential of archived F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Previous SAA studies have reported the detection of misfolded αSyn in formaldehyde-fixed human tissue of PD, incidental LBD and MSA subjects and more recently, Hepker et al developed a kinetic assay seeding ability recovery (KASAR) protocol using FFPE core of globus pallidus with great sensitivity and specificity [50][51][52]. However, despite the successful findings, brain tissues were fixed for a relatively short amount of time (18 hours) or in a less concentrated formaldehyde solution (4%) or fixed in paraformaldehyde that does not penetrate the tissue as rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Previous SAA studies have reported the detection of misfolded αSyn in formaldehyde-fixed human tissue of PD, incidental LBD and MSA subjects and more recently, Hepker et al developed a kinetic assay seeding ability recovery (KASAR) protocol using FFPE core of globus pallidus with great sensitivity and specificity [50][51][52]. However, despite the successful findings, brain tissues were fixed for a relatively short amount of time (18 hours) or in a less concentrated formaldehyde solution (4%) or fixed in paraformaldehyde that does not penetrate the tissue as rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Previous SAA studies have reported the detection of misfolded αSyn in formaldehyde-fixed human tissue of PD, incidental LBD and MSA subjects and more recently, Hepker et al developed a kinetic assay seeding ability recovery (KASAR) protocol using FFPE core of globus pallidus with great sensitivity and specificity [ 51 , 52 , 53 ]. However, despite the successful findings, brain tissues were fixed for a relatively short amount of time (18 h) or in a less concentrated formaldehyde solution (4%) or fixed in paraformaldehyde that does not penetrate the tissue as rapidly.…”
Section: Discussionmentioning
confidence: 99%